Development of raft-forming liquid and chewable tablet formulations incorporating quercetin solid dispersions for treatment of gastric ulcers - Suputra Bunlung; Teerapat Nualnoi; Ousanee Issarachot; Ruedeekorn Wiwattanapatapee (Elsevier, 2021)
Gastroretentive raft-forming formulations were developed in liquid and chewable tablet dosage forms to achieve prolonged delivery of quercetin in the stomach. The formulations contained a solid dispersion of quercetin and polyvinylpyrrolidone (PVP K 30) at a 1:10 w/w ratio to improve the solubility of the flavonoid. The formulations also contained sodium alginate as a gel forming agent, calcium carbonate as a calcium source and carbon dioxide producer and hydroxypropyl methylcellulose K100M as a drug release retarding polymer. The chewable tablets incorporated mannitol as a diluent. Both liquid and chewable tablet formulations exhibited rapid floating behaviour (lag time < 1 min) and long floating duration (>24 h) in 0.1 N HCl. The optimized liquid formulation showed superior characteristics based on high raft strength (10.4 g) and sustained release of quercetin (93 % over 8 h) whereas the optimized chewable tablet formulation exhibited lower raft strength (7.2 g) and lower drug release (79 % in 8 h). The optimized liquid and chewable tablet formulations were found to induce anti-inflammatory activity in cell culture using RAW 264.7 cells macrophages and enhance the migration of human gastric adenocarcinoma (AGS) epithelial cells in vitro, indicating wound healing potential for treatment of gastric ulcers.